2015
DOI: 10.1186/s40064-015-0837-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling inflation rates and exchange rates in Ghana: application of multivariate GARCH models

Abstract: This paper was aimed at investigating the volatility and conditional relationship among inflation rates, exchange rates and interest rates as well as to construct a model using multivariate GARCH DCC and BEKK models using Ghana data from January 1990 to December 2013. The study revealed that the cumulative depreciation of the cedi to the US dollar from 1990 to 2013 is 7,010.2% and the yearly weighted depreciation of the cedi to the US dollar for the period is 20.4%. There was evidence that, the fact that infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
3
23
0
3
Order By: Relevance
“…The most popular Multivariate GARCH models are the diagonal BEKK, the diagonal VECH, CCC and DCC models. For a Multivariate time series Y y , y , y , … , y the Multivariate GARCH model is given by y = P / ε ( 1 ) where P denotes a k × k positive definite matrix and of the conditional variance of C t , k represent the number of series and t = 1,2,…,n where n is the number of observations (Nortey et al, 2015). It is with the specification of conditional variance that the Multivariate GARCH model changes.…”
Section: Multivariate Garch Modelmentioning
confidence: 99%
“…The most popular Multivariate GARCH models are the diagonal BEKK, the diagonal VECH, CCC and DCC models. For a Multivariate time series Y y , y , y , … , y the Multivariate GARCH model is given by y = P / ε ( 1 ) where P denotes a k × k positive definite matrix and of the conditional variance of C t , k represent the number of series and t = 1,2,…,n where n is the number of observations (Nortey et al, 2015). It is with the specification of conditional variance that the Multivariate GARCH model changes.…”
Section: Multivariate Garch Modelmentioning
confidence: 99%
“…A Structural Vector Error Correction Analysis was used in their investigations. Nortey et al (2015) investigated the volatility and conditional relationship among inflation rates, exchange rates and interest rates using multivariate GARCH DCC and BEKK models using Ghana data from January 1990 to December 2013. The study revealed that the cumulative depreciation of the cedi to the US dollar from 1990 to 2013 is 7,010.2% and the yearly weighted depreciation of the cedi to the US dollar for the period is 20.4%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relative demand for currencies reflects the causal demand for goods and services denominated in that currency. Depreciation in the currency value causes imported commodities to become relatively expensive, worsening the economy, especially if the country depends heavily on imports (Nortey et al, 2015). International capital flows can also have a strong influence on the demand for various currencies (Ehlers & Takas, 2013).…”
Section: Introductionmentioning
confidence: 99%